PREFIKSASI DALAM LIRIK LAGU BUKTI DAN SELAMAT TINGGAL PADA ALBUM SURAT CINTA UNTUK STARLA - Mulyana, Devina; Hasanah, Elsa Kholifatul; Ulfah, Fadilla; Nurjam’an , Muhammad Ichsan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
This research is motivated by the importance of understanding morphological processes, especially affixation, which plays a role in the formation and meaning of words in Indonesian. Amidst the rise of language errors among teenagers due to the influence of popular language, examples of the use of correct language forms are needed. This study aims to describe the prefix forms in two Virgoun songs in the album Surat Cinta untuk Starla, namely